Effect of Right Insular Involvement on Death and Functional Outcome After Acute Ischemic Stroke in the IST-3 Trial (Third International Stroke Trial). Issue 12 (December 2016) - Sposato, Luciano A.; Cohen, Geoffrey; Wardlaw, Joanna M.; Sandercock, Peter; Lindley, Richard I.; Hachinski, Vladimir; von Kummer, Rudiger; von Heijne, Anders; Bradey, Nick; Peeters, Andre; Cala, Lesley; Adami, Alessandro; et al.
Abstract : Background and Purpose—: In patients with acute ischemic stroke, whether involvement of the insular cortex influences outcome is controversial. Much of the apparent adverse outcome may relate to such strokes usually being severe. We examined the influence of right and left insular involvement on stroke outcomes among patients from the IST-3 study (Third International Stroke Trial) who had visible ischemic stroke on neuroimaging. Methods—: We used multiple logistic regression to compare outcomes of left versus right insular and noninsular strokes across strata of stroke severity, on death, proportion dead or dependent, and level of disability (ordinalized Oxford Handicap Score) at 6 months, with adjustment for the effects of age, lesion size, and presence of atrial fibrillation. Results—: Of 3035 patients recruited, 2099 had visible ischemic strokes limited to a single hemisphere on computed tomography/magnetic resonance scans. Of these, 566 and 714 had infarction of right and left insula. Six months after randomization, right insular involvement was associated with increased odds of death when compared with noninsular strokes on the left side (adjusted odds ratio, 1.83; 95% confidence interval, 1.33−2.52), whereas the adjusted odds ratio comparing mortality after insular versus noninsular strokes on the left side was not significant. Among mild/moderate strokes, outcomes for right insular involvement were worse than for left insular, but among more severe strokes, the difference in outcomes was less substantial. Conclusions—: We found an association between right insular involvement and higher odds of death and worse functional outcome. The difference between right- and left-sided insular lesions on outcomes seemed to be most evident for mild/moderate strokes. Clinical Trial Registration—: URL:http://www.isrctn.com . Unique identifier: ISRCTN25765518. Abstract : Supplemental Digital Content is available in the text.